Determination of Maqasid Al-Syari’ah In The Requirements For Pre-Marriage Health Check With The Tahqiq Al-Manat Approach - ahmad, zuhdi; Danial; Taufiqulhadi (Yayasan Pendidikan dan Kemanusiaan Hurriah Aceh, 2025)
This study examines the application of the Ta?qiq al-Manat methodological framework in determining the essential categories and priority levels of Maqasid al-Syari’ah in premarital health evaluations. It emphasizes the necessity of applying Maqasid al-Syari’ah in a casuistic manner to modern challenges, highlighting the absence of a systematic framework for its implementation in premarital health examinations. The study employs a library research method with documented data gathering, utilizing a taxonomy approach and descriptive analysis. Research indicates that establishing the essential categories of Maqasid al-Syari’ah involves: (1) identifying the al-Manat object, encompassing seven categories of premarital assessments; (2) validating al-Manat via medical expert opinions and the principle of al-Daf‘u ashal min al-raf‘i; and (3) delineating Maqasid al-Syari’ah through rational premises substantiated by empirical results. Establishing priority levels entails: (1) delineating three priority tiers; (2) corroborating through the viewpoints of potential couples and governmental entities; and (3) evaluating priorities utilizing pertinent instruments linked with the research topic. The study finds that delineating the categories and priorities of Maqasid al-Syari’ah in a case-specific context necessitates a dynamic Ta?qiq al-Manat framework and a variety of instruments to tackle contemporary difficulties in Islamic law, especially regarding premarital health evaluations.